2014
DOI: 10.1155/2014/968141
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Roles of Prostaglandins in Blastocyst Implantation

Abstract: Prostaglandins (PGs), derivatives of arachidonic acid, play an indispensable role in embryo implantation. PGs have been reported to participate in the increase in vascular permeability, stromal decidualization, blastocyst growth and development, leukocyte recruitment, embryo transport, trophoblast invasion, and extracellular matrix remodeling during implantation. Deranged PGs syntheses and actions will result in implantation failure. This review summarizes up-to-date literatures on the role of PGs in blastocys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 158 publications
1
49
0
3
Order By: Relevance
“…In addition to Itga4, many other plasma membrane receptors exhibited altered expression levels in uterine GR KO mice. Prostaglandins also have an important role as signaling molecules in the early events of implantation and decidualization, and both prostaglandin I2 receptor (Ptgir) and prostaglandin E receptor 4 (Ptger4) were down-regulated in uterine GR KO mice following the decidualization stimulus (19). Although neither of these genes has been previously shown to be regulated by glucocorticoids, we found that Ptgir was significantly regulated by dexamethasone in our microarray in the uterus of control mice.…”
Section: Discussionmentioning
confidence: 55%
“…In addition to Itga4, many other plasma membrane receptors exhibited altered expression levels in uterine GR KO mice. Prostaglandins also have an important role as signaling molecules in the early events of implantation and decidualization, and both prostaglandin I2 receptor (Ptgir) and prostaglandin E receptor 4 (Ptger4) were down-regulated in uterine GR KO mice following the decidualization stimulus (19). Although neither of these genes has been previously shown to be regulated by glucocorticoids, we found that Ptgir was significantly regulated by dexamethasone in our microarray in the uterus of control mice.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, the pattern of COX-2 expression in the pregnant rat uterus suggests a fundamental role during embryo implantation and decidualization [4,5]. In animal models, PG signaling has been implicated in increased vascular permeability, stromal decidualization, embryo development, and extracellular matrix remodeling during implantation [3]. However, in humans, till now little is known about the role of PGs in decidualization.…”
Section: Discussionmentioning
confidence: 99%
“…PGs, derived from cyclooxygenase-2 (COX-2), are believed to play an important role in regulating decidualization, angiogenesis, vascular remodeling, trophoblast invasion, and extracellular matrix remodeling during implantation [3]. In rats, COX-2 expression is mostly restricted to implantation sites, and COX-2 2/2 mice are infertile, with defective implantation and decidualization [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that in estrogen pretreated uteri, other factors, for example, LIF (Salleh and Giribabu 2014) and prostaglandins (PGs) (Salleh 2014) could be involved in controlling V-ATPase expression under progesterone influence. These paracrine regulations could help to optimize the pH needed for embryo implantation.…”
Section: Discussionmentioning
confidence: 99%